Assessing Scientific Claims In Print Ads that Promote Cosmetics - Fowler, Jie G.; Carlson, Les; Chaudhuri, Himadri Roy (Journal of Advertising Research, 2019)
The area of scientific-related claims in advertising is ripe for additional investigative endeavor. This article aims to access the nature and potential deceptiveness of scientific-related claims that appear in cosmetics advertising. To examine these claims, the authors used perceptions of actual cosmetics consumers as well as of licensed physicians. The findings suggest that the decision making of cosmetics consumers could be enhanced by the addition to cosmetics advertising of information about certain cosmetics claims.